(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2020)
The article analyzes and criticizes the assumptions of Peter Van Inwagen’s argument for the alleged contradiction of the foreknowledge of God and human freedom. The argument is based on the sine qua non condition of human freedom defined as access to possible worlds containing such a continuation of the present in which the agent implements a different action than will be realized de facto in the future. The condition also contains that in every possible continuation of the present state of affairs, the same propositions about the ‘present past’ (the past before the present moment) are true as are true in the present state of affairs. The paper argues that Van Inwagen’s reasoning is inconclusive, it contains the type of mistake of confusing conditional impossibility with unconditional and presents a methodologically wrong method of solving a philosophical problem. It is because in the very construction of the problem determining the available solution. The article points to the possibility that the human freedom of some action is not excluded by the fact that specific past facts logically entail that this event will occur.